The symbolism of the motif Malay cucuk sanggul - Isnin, Aiqa Afiqah; Ab Aziz, Arbai’yah; Abd Aziz, Mohamad Kamal (Faculty of Art and Design, 2025)
Cucuk Sanggul is a type of Malay accessories made from materials such as gold, silver, copper, wood, and others. Its purpose is to secure the hair in place, keeping it neat and tidy. Head accessories like Cucuk Sanggul serve as symbols of status, grandeur, and luxury in traditional Malay clothing. Cucuk Sanggul is categorized as a traditional accessory used by Malay women in the Nusantara. Research indicates that this craft is nearly extinct due to a lack of interest and skill among younger generations, and the design of Cucuk Sanggul has become outdated in the modern world. The objectives of the study focus on the design of Cucuk Sanggul within the context of Malay identity and women’s civilization and identifying the types and symbolism of the Cucuk Sanggul motifs. A qualitative approach through interviews was used in this research. The study also utilizes several samples of Cucuk Sanggul from museum collections as primary sources. The findings from this research can serve as documentation material and help preserve the design of Cucuk Sanggul within the context of national heritage art.